MEASURES FOR TOURISM FACILITIES DEVELOPMENT IN UZBEKISTAN AFTER THE PANDEMIC, AND ITS EFFECT TO THE ECONOMY - Yuldasheva, Dilnoza; Odilov, Jakhongir (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
As a leading sector of the global economy, tourism today has a significant contribution to the socio-economic development of countries, and to the economy itself, as tourism contributes more than 11% GDP of world economy. Accordingly, the article offers fifteen major measures to the development of tourism facilities in Uzbekistan after the full escape from COVID-19 pandemic, and analyzes its effect to the country’s economy.